Integrating Spatial Risk Mapping and Environmental Law for Drought Adaptation in Grobogan, Indonesia - Tjahjono, Heri; Hanafi, Fahrudin; Kalyana Putri, Enda; bin Nayan, Nasir; Afrilianto, Adit (Universitas Negeri Semarang, 2025)
This research investigates drought risk in Grobogan Regency, Central Java Province, by linking spatial evidence, social capacity, and legal frameworks to the advancement of the Sustainable Development Goals (SDGs). A hazard–vulnerability–capacity approach, grounded in Geographic Information Systems (GIS), is combined with surveys, Focus Group Discussions (FGDs), and policy analysis. The study generates a risk map identifying priority subdistricts for intervention. Findings indicate fragmented capacity and institutional arrangements across regions, which undermine the effectiveness of drought response. Regulatory analysis reveals implementation gaps between national legal provisions on water resource and disaster management and their operationalization at the regional and village levels. A Comparative analysis of water resource management practices in Malaysia identifies opportunities to harmonize policies and legal instruments, thereby facilitating the translation of spatial findings into actionable local policies. Policy recommendations include strengthening local regulations (Perda) for emergency water allocation, integrating risk maps into the Regional Medium-Term Development Plan (RPJMD) and village development plans, operationalizing community-based early warning systems (EWS), and establishing hybrid financing mechanisms (APBD–APBDes–grants) for water conservation infrastructure. The primary contribution is the demonstration of integrating spatial analysis and legal studies to inform drought adaptation policies that support SDG indicators, particularly SDG 6 (Clean Water and Sanitation), SDG 2 (Zero Hunger), and SDG 13 (Climate Action). Implementation recommendations encompass measurable monitoring indicators, local capacity-building, periodic evaluations, cross-sector collaboration, and transparent public reporting.